2015
DOI: 10.1016/j.chemosphere.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the contributions of polychlorinated dibenzo-p-dioxins and dibenzofurans and other unintentionally produced persistent organic pollutants to the total toxic equivalents in air of steel plant areas

Abstract: h i g h l i g h t sLevel of dioxin and dioxin-like compounds in air of steel plant areas was studied. Relative contribution of dioxins and dioxin-like compounds was compared. Profiles of dioxins and dioxin-like compounds in the ambient air were stated. a r t i c l e i n f o , and 0.02-0.12 pg TEQ N m À3 , respectively. The PCNs were the most abundant compounds (by mass concentration), contributing about 87% of the total mass concentrations of the analytes that were found in the air of the steel plant areas. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…As shown in Fig. 6(b), the PBDFs, especially the higher brominated PBDFs, were the dominant PBDD/F congeners in the particles in every size range Li et al, 2015a). The fraction of the higher brominated PBDFs in the particulate phase decreased as the particle size increased, but that was not the case for the PBDDs.…”
Section: Pcdd/f Homolog and Pbdd/f Congener Profile Distributions Formentioning
confidence: 82%
See 3 more Smart Citations
“…As shown in Fig. 6(b), the PBDFs, especially the higher brominated PBDFs, were the dominant PBDD/F congeners in the particles in every size range Li et al, 2015a). The fraction of the higher brominated PBDFs in the particulate phase decreased as the particle size increased, but that was not the case for the PBDDs.…”
Section: Pcdd/f Homolog and Pbdd/f Congener Profile Distributions Formentioning
confidence: 82%
“…The results showed that the PCDD/Fs were adsorbed onto the particles. In this study and in a previous study (Li et al, 2015a), the PBDFs were the main contributors to the PBDD/Fs. The PBDF distributions in the particles of different sizes were therefore also studied (Table 3).…”
Section: Relationship Between the Gas/particle Partitioning Of The Pxmentioning
confidence: 92%
See 2 more Smart Citations
“…The unintentional production of PCNs during thermal processes has already been the main source of PCNs in ambient air. Previous studies have reported larger amounts of PCNs than PCDD/Fs were emitted during various thermal processes [9,10]. Therefore, studies of PCN emissions during different thermal processes are of significance necessary.…”
Section: Introductionmentioning
confidence: 99%